Reflexões sobre o ensino de libras no atendimento educacional especializado na cidade de Caraúbas/RN - Silva, Bianca Sonale Fonseca da (Universidade Federal Rural do Semi-Árido, 2018)
In this work the main objective was to discuss the teaching of LIBRAS, aimed at deaf students, carried out in the Specialized Educational Service, in schools in the city of Caraúbas / RN. From a theoretical point of view, we support our study in the Legislation, which governs the regularization of LIBRAS, as the first language of the deaf person, as well as in Decree 5,626 / 2005, which legislates on the inclusion of LIBRAS in the regular school. It is a qualitative research in education (ANDRÉ & LUCKE, 2015), in which we make a participant observation and open interviews. With regard to the procedure for the selection of participants, locus and data collection, we carried out visits to schools, we elaborated a questionnaire with questions regarding the academic formation of the teachers, the time of service in the Specialized Educational Service, to the knowledge of the Deaf Culture, among others. In our findings, we highlight three thematic categories: Contact with LIBRAS and knowledge of the Deaf Culture, in which we find fragilities in the relations between the teachers who work in the ESA and the first language of the deaf; Teaching materials, the teachers presented the types used in teaching to deaf students, among them, videos, alphabets, games, etc.; and, finally, the notes on the EEE to deaf students, where the participants emphasized the importance of more human resources in the ESA (interpreters / translators) and technological material resources. From the reports of both teachers we realized that there is a common understanding that ESA for the deaf student depends on a structural intervention, related to human and pedagogical resources for multifunctional resource rooms. One of the data that aroused curiosity was the fact that in none of the narratives did the demand arise to review the pedagogical practices used with the deaf students served.
Monografia
Keywords: Ensino de Libras; Atendimento Educacional Especializado; Prática Pedagógica; LINGUISTICA, LETRAS E ARTES::LETRAS::LETRAS LIBRAS